Icanbelimod (CBP-307), a next-generation Sphingosine-1-phosphate receptor modulator, in healthy men: pharmacokinetics, pharmacodynamics, safety, and tolerability in a randomized trial in Australia - Lickliter, Jason; Yang, Xin; Guo, Jiawang; Pan, Wubin; Wei, Zheng (Frontiers in Immunology, 2024)
Background: Icanbelimod (formerly CBP-307) is a next-generation S1PR modulator, targeting S1PR1. In this first-in-human study, icanbelimod was investigated in healthy men in Australia.Methods: Participants were randomized 3:1, double-blind, to icanbelimod or placebo in four singledose cohorts (0.1 mg, 0.25 mg, 0.5 mg [n=8 per cohort], 2.5 mg [n=4]) or for 28-days once-daily treatment in two cohorts (0.15 mg, 0.25 mg [n=8 per cohort]). Participants in the 0.25-mg cohort received 0.1 mg on Day 1. Treatments were administered orally after fasting; following one-week washout, icanbelimod was administered after breakfast in the 0.5-mg cohort.Results: Icanbelimod exposure increased rapidly and dose-proportionally dependently with single and multiple dosing (Tmax 4-7 hours). Lymphocyte counts decreased rapidly after single (-11%, 0.1 mg; -40%, 0.25 mg; -71%, 0.5 mg; -77%, 2.5 mg) and multiple doses (-49%, 0.15 mg; -75%, 0.25 mg), and recovered quickly, 7 days after dosing. After single-dose 0.5 mg, although a high-fat breakfast versus fasting did not affect maximal decrease, lymphocyte counts tended to be lower after breakfast across most timepoints up to 72 hours. Twenty-eight participants (63.6%) experienced mainly mild treatment-emergent adverse events (TEAEs). After single-dose icanbelimod, the most common TEAEs were headache (28.6%, n=6) and dizziness (19.0%, n=4). Three participants experienced transient bradycardia, with one serious, all following single-dose 2.5 mg icanbelimod. After multipledose icanbelimod, the most common TEAEs were headache (50.0%, n=6) and lymphopenia (41.7%, n=5), and two participants withdrew due to non-serious TEAEs. Up-titration attenuated heart rate reductions.Icanbelimod was well-tolerated up to 0.5 mg and effectively reduced lymphocyte counts.